04. Immunogenicity and Safety of a Quadrivalent Meningococcal Conjugate Vaccine (MenACYW-TT) Administered in Meningococcal Vaccine-Naive Participants Across a Broad Age Range (2-55 Years) in Japan. (4th December 2021) - Matsuoka, Osamu; Ujiie, Mugen; Kikuchi, Hitoshi; Chansinghakul, Danaya; Inoue, Takahiro; Varghese, Kucku; Sirisuphmitr, Nuchra; Hashiguchi, Tomoyuki; Zambrano, Betzana; Nakama, Takahiro; Frago, Carina; Jordanov, Emilia; et al.
Abstract: Background: MenACYW-TT [MenQuadfi ® ] is a quadrivalent meningococcal conjugate vaccine, licensed for use in ages 2 years and older in USA. The vaccine is also licensed in ages 12 months and older in EU and certain other countries. We evaluated the safety and immunogenicity of MenACYW-TT compared to a licensed quadrivalent conjugate meningococcal vaccine (MenACWY-DT [Menactra ® ]) in Japanese children, adolescents and adults (2-55 years of age). Methods: A phase III modified double-blind, randomized study (NCT04368429) to evaluate the immunogenicity and safety of a single dose of MenACYW-TT versus MenACWY-DT was conducted in 360 participants (ratio 1:1) between ages 2 and 55 years in Japan. Serum bactericidal assays with human complement (hSBA) were used to measure antibodies against vaccine serogroups at baseline (Day 0) and 30 days post-vaccination (D30). Safety data were collected up to 30 days post-vaccination. Results: Non-inferiority of immune responses for all four serogroups, based on percentages of participants achieving hSBA vaccine seroresponse as primary endpoint, was demonstrated for MenACYW-TT compared to MenACWY-DT at Day 30 in comparison to baseline: 85.6% vs 65.4% for serogroup A, 96.6% vs 62.6% for serogroup C, 87.4% vs 49.2% for serogroup W, and 97.7% vs 63.5% for serogroup Y. The proportions of individuals with hSBA titers ≥ 1:8 following MenACYW-TT administration were higher than those after MenACWY-DT administration for serogroups C (98.9% vs 81.0%), W (99.4% vs 91.1%) and Y (100 % vs 89.4%) and comparable for serogroup A (96.6% vs 92.7%). The hSBA GMTs were higher following administration of MenACYW-TT for all four serogroups. Immunogenicity results in participants 10 to 17 years of age and ≥ 18 years of age were comparable to those in the whole population (2-55 years). The safety profiles of MenACYW-TT and MenACWY-DT were comparable. There were no immediate adverse events (AEs), no AEs leading to study discontinuation, and no vaccine-related serious adverse events reported in the study. Conclusion: MenACYW-TT vaccine was well tolerated and demonstrated a non-inferior immune response compared to that for the licensed MenACWY-DT vaccine when administered as a single dose to meningococcal vaccine-naïve children, adolescents, and adults in Japan. Disclosures: Osamu Matsuoka, MD, Sanofi Pasteur (Scientific Research Study Investigator, Research Grant or Support) Mugen Ujiie, MD, Sanofi Pasteur (Scientific Research Study Investigator, Research Grant or Support) Hitoshi Kikuchi, MD, Sanofi Pasteur (Scientific Research Study Investigator)Sanofi Pasteur (Research Grant or Support) Danaya Chansinghakul, MD, Sanofi Pasteur (Employee) Takahiro Inoue, MSc, Sanofi Pasteur (Employee) Kucku Varghese, PhD, Sanofi Pasteur (Employee) Nuchra Sirisuphmitr, MSc, Sanofi Pasteur (Employee) Tomoyuki Hashiguchi, MSc, Sanofi Pasteur (Employee) Betzana Zambrano, MD, Sanofi Pasteur (Employee) Takahiro Nakama, MD, Sanofi Pasteur (Employee) Carina Frago, MD, Sanofi Pasteur (Employee, Shareholder) Emilia Jordanov, MD, Sanofi Pasteur (Employee, Shareholder) Mandeep S. Dhingra, MD, Sanofi Pasteur (Employee, Shareholder)